Edukasi Mengenai Tanda – Gejala Serangan Jantung pada Keluarga Pasien Ruang Rawat Inap Rumah Sakit Swasta di Kota Medan - Agus Surya Bakti; Ani Rahmadhani Kaban; Muflih Muflih; Maya Ardilla Siregar (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
The family is the first person if the patient experiences a heart attack. The results of the study show that there is a relationship between family attitudes and actions regarding the incidence of heart attacks. The family has a very important role in patient care. This can be interpreted as meaning that family involvement in handling heart attacks needs to be carefully considered. The family can experience all the problems, confusion, lack of knowledge and obstacles when helping someone who has had a heart attack. This heart attack can occur anywhere and at any time. Often people are late in carrying out initial treatment, seeking information and help. The situation that occurs in society, most people are not aware of the symptoms of a heart attack. So people don't know if they are having a heart attack, receive treatment late, and even die before arriving at the hospital.